Evaluation of Coagulometric Assays in the Assessment of Protein C Anticoagulant Activity; Variable Sensitivity of Commercial APTT Reagents to the Cofactor Effect of Protein S - D'Angelo, Silvana Viganó; Gilardoni, Felicia; D'Angelo, Armando (Thrombosis and Haemostasis, 1989)
In vivo expression of protein C activity is dependent on the availability of the activated protein C (APC) cofactor protein S. In the clinical laboratory, measurement of protein C anticoagulant activity is mostly performed in modified APTT assays. We have evaluated 13 commercial APTT reagents for their sensitivity to the cofactor effect of protein S by comparing APC-dependent clotting time prolongations in normal plasma and in protein S depleted plasma. In normal plasma, the sensitivities of the APTT reagents to the anticoagulant effect of APC were markedly different and correlated with the sensitivity of reagents to factor V and VIII. Reagents containing soy phosphatides appeared more sensitive than reagents containing phospholipid of animal origin. Analysis of dose-response curves obtained in normal plasma distinguished one group of reagents showing clotting time prolongations linearly related to the APC concentrations, a second group showing a log-linear relationship and a third group showing a log-log relationship. In protein S depleted plasma, sensitivity of APTT reagents to APC was in general proportional to that observed in normal plasma. However, for some reagents dose-response curves were qualitatively different in normal and in protein S depleted plasma. With all the APTT reagents, APC-dependent clotting time prolongations corresponding to 30-80% of APC anticoagulant activity observed in normal plasma, were observed in protein S depleted plasma. At variance, in a modified Xa one-stage clotting assay, negligible clotting time prolongations were observed in protein S depleted plasma, indicating that over 90% of the APC anticoagulant activity was protein S dependent in this assay system. Dilution of a relative insensitive APTT reagent effectively increased its sensitivity to the cofactor effect of protein S, suggesting that different phospholipid content and/or composition might be responsible for the different sensitivity of APTT reagents to protein S.These results question the validity of APTT based assays for the identification of qualitative protein C abnormalities with defective interaction with protein S.
Keywords: Protein C; Protein S; Protein C coagulometric assays